Survival rate and growth performance of tilapia (Oreochromis niloticus) exposed in polyvinyl chloride microplastics - Bagus Dwi Hari Setyono; Wiwin Iky Soenarky; Zaenal Abidin; Rangga Idris Affandi (Depik, 2024)
Plastic is one of the materials most widely used by humans. The more plastic that is used, the more plastic waste is released into environment and will polute water areas in various sizes, both macroplastics and microplastics. Microplastic are classified as plastic particles whose diameter is less than 5 millimeters. One type of microplastic that has an adverse impact on the life of aquatic organisms is polyvinyl chloride (PVC). The aim of this research was to determine the effect of PVC microplastic exposure on the survival rate and growth performance of tilapia, Oreochromis niloticus. This study was conducted in a completely randomized design (CRD) consisting of four treatments with three replications. The treatments were as follows: MP0 = No addition of microplastics (control); MP1 = Addition of 5 mg/L microplastics; MP2 = Addition of 15 mg/L microplastics; MP3 = Addition of 20 mg/L microplastics. The results showed that exposure to polyvinyl chloride microplastics on the survival rate and growth performance of tilapia through water made a real difference to Survival Rate (SR), absolute weight growth, absolute length growth, Specific Growth Rate (SGR), Feed Convension Ratio (FCR) and the abundance of polyvinyl chloride microplastics in fish gut.Keywords:MicroplasticPolyvinyl chlorideTilapiaSurvival rateGrowth performance